Molecular genetic evaluation of pediatric renovascular hypertension due to renal artery stenosis and abdominal aortic coarctation in neurofibromatosis type 1. Issue 3 (2nd September 2021) - Coleman, Dawn M; Wang, Yu; Yang, Min-Lee; Hunker, Kristina L; Birt, Isabelle; Bergin, Ingrid L; Li, Jun Z; Stanley, James C; Ganesh, Santhi K
Abstract: The etiology of renal artery stenosis (RAS) and abdominal aortic coarctation (AAC) causing the midaortic syndrome (MAS), often resulting in renovascular hypertension (RVH), remains ill-defined. Neurofibromatosis type 1 (NF-1) is frequently observed in children with RVH. Consecutive pediatric patients ( N = 102) presenting with RVH secondary to RAS with and without concurrent AAC were prospectively enrolled in a clinical data base, and blood, saliva and operative tissue, when available, were collected. Among the 102 children, 13 were having a concurrent clinical diagnosis of NF-1 (12.5%). Whole exome sequencing was performed for germline variant detection, and RNA-Seq analysis of NF1, MAPK pathway genes and MCP1 levels were undertaken in five NF-1 stenotic renal arteries, as well as control renal and mesenteric arteries from children with no known vasculopathy or NF-1. In 11 unrelated children with sequencing data, 11 NF1 genetic variants were identified, of which 10 had not been reported in gnomAD. Histologic analysis of NF-1 RAS specimens consistently revealed intimal thickening, disruption of the internal elastic lamina and medial thinning. Analysis of transcript expression in arterial lesions documented an approximately 5-fold reduction in NF1 expression, confirming heterozygosity, MAPK pathway activation and increased MCP1 expression. In summary, NF-1-related RVH in children is rare but often severe and progressive and, as such, important to recognize. It is associated with histologic and molecular features consistent with an aggressive adverse vascular remodeling process. Further research is necessary to define the mechanisms underlying these findings.